Imaging Nerve Pathology of the Knee: Magnetic Resonance Imaging and Ultrasound - Morag, Yoav; Yang, Lynda J.S. (Seminars in Musculoskeletal Radiology, 2017)
Peripheral neuropathies are not uncommon, and the diagnostic evaluation includes a clinical assessment and electrophysiologic studies as well as diagnostic imaging. Magnetic resonance imaging (MRI) and high-resolution ultrasound (HRUS) are of special importance in providing the surgeon with information in the context of nerve trauma, entrapment, and nerve involvement by tumors. Peripheral neuropathy about the knee can occur in the context of associated knee pathology such as trauma, as part of a systemic disease, or as an isolated finding. In this review, we discuss the role of MRI and HRUS in the evaluation of peripheral neuropathy and present imaging examples of peripheral neuropathy involving the knee.
Keywords: neuropathy; knee; MRI; ultrasound